Mode I interlaminar fracture of woven glass/epoxy multidirectional laminates - Pereira, A.B.
Mode I Double Cantilever Beam (DCB) tests were performed on woven glass/epoxy multidirectional laminates. Selected specimen stacking sequences with starter delaminations in theta/-theta and 0/theta interfaces were first evaluated with three-dimensional finite element (FE) models. During the DCB tests, most specimens suffered intraply damage and crack branching to a neighbouring interface. Nevertheless, it was generally possible to measure valid interlaminar critical strain energy release rates, G(IC), of initiation from the film and from a mode I precrack. The former were significantly lower than the latter due to steep R-curve effects. G(IC) values of 0/theta specimens were fairly theta-independent, while theta/-0 specimens exhibited higher G(IC) from the film. A subsequent FE analysis provided explanations for the interface effect on G(IC).